2017
DOI: 10.1016/j.neuroimage.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the pharmacological modulation of brain oxygen metabolism: The effects of caffeine on absolute CMRO2 measured using dual calibrated fMRI

Abstract: This study aims to map the acute effects of caffeine ingestion on grey matter oxygen metabolism and haemodynamics with a novel MRI method. Sixteen healthy caffeine consumers (8 males, age=24.7±5.1) were recruited to this randomised, double-blind, placebo-controlled study. Each participant was scanned on two days before and after the delivery of an oral caffeine (250mg) or placebo capsule. Our measurements were obtained with a newly proposed estimation approach applied to data from a dual calibration fMRI exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 62 publications
4
56
0
Order By: Relevance
“…These apparent total GM changes emphasize the importance of controlling for caffeine consumption in repeated fMRI measures, especially with a region of interests in the most impacted regions (cuneus, precuneus, cerebellum, and subcortices). The observation of the typical caffeine-induced reductions in CBF 42,57,58 in our study, moreover add to the current knowledge that the history of caffeine intake at least within 4.5 hours strongly impacts on both CBF and apparent tissue change.…”
Section: Discussionsupporting
confidence: 78%
“…These apparent total GM changes emphasize the importance of controlling for caffeine consumption in repeated fMRI measures, especially with a region of interests in the most impacted regions (cuneus, precuneus, cerebellum, and subcortices). The observation of the typical caffeine-induced reductions in CBF 42,57,58 in our study, moreover add to the current knowledge that the history of caffeine intake at least within 4.5 hours strongly impacts on both CBF and apparent tissue change.…”
Section: Discussionsupporting
confidence: 78%
“…gray matter), while the opposite was found in the white matter and lower part of the brain. Our results are consistent with previous ASL findings, which reported that decreasing CBF were widespread in the grey matter after caffeine intake (Buch et al 2017; Merola et al 2017). Compared to the delay map difference shown in Figure 5.a, we found that the regions of vessel constriction after caffeine intake overlap largely with the regions where the blood flow speed increases.…”
Section: Discussionsupporting
confidence: 93%
“…The CSF regions of interest (ROI) was obtained in native space based on a surface‐based atlas using FreeSurfer following cortical reconstruction . Estimated values of CBF were masked within range (0‐200) mL/100 g/minute to exclude implausible physiologic values . Baseline CBF and BOLD values were then averaged across time to reduce variability and maximize statistical power.…”
Section: Methodsmentioning
confidence: 99%
“…29 Estimated values of CBF were masked within range (0-200) mL/100 g/minute to exclude implausible physiologic values. 30 Baseline CBF and BOLD values were then averaged across time to reduce variability and maximize statistical power. Lesion and perimeter 1-4 masks were applied to average baseline CBF and BOLD maps to obtain average BOLD and CBF in and around MS lesions.…”
Section: Dual-echo Cfmri Processingmentioning
confidence: 99%